AP1-mediated reprogramming of EGFR expression triggers resistance to BLU-667 and LOXO-292 in RET-rearranged tumors - Daniela Esposito; Claudia Maria Ascione; Stefania Belli; Fabiana Napolitano; Alberto Servetto; Felice Pepe; Umberto Malapelle; Antonino Iaccarino; Giancarlo Troncone; Diletta Barone; Emilio Bria; Roberto Ferrara; et al. (Journal of Experimental & Clinical Cancer Research)
Abstract Background Non-small cell lung cancer (NSCLC) is a significant global health challenge, with 2% of cases fuelled by RET rearrangements. RET inhibitors (RETi) have revolutionized treatment for these patients, but resistance remains an important clinical challenge limiting therapy effectiveness. This study investigated the mechanisms underlying resistance to RETi. Methods NSCLC cells were exposed to increasing doses of RETi (pralsetinib/BLU-667 and selpercatinib/LOXO-292) to generate resistant cells. RNA-Sequencing analysis identified differentially expressed genes in resistant versus sensitive cells, followed by in vitro and in vivo functional assays to explore novel therapeutic strategies. Additionally, tumor biopsies from RET-rearranged NSCLC patients who exhibited cancer progression on RET inhibitor therapy were analyzed. Results RNA-sequencing analysis revealed the upregulation of the EGFR signaling pathway and hyperactivation of AP1 complex members in resistant cells compared to sensitive cells. Silencing of EGFR and AP1 complex members significantly reversed drug resistance, whereas EGFR overexpression reduced the sensitivity of parental Lc2/AD cells to RET inhibitors. Furthermore, the combination of RET and EGFR inhibitors showed synergistic antitumor activity in vitro and hindered tumor growth in mouse models with resistant cell xenografts. Notably, we observed a significant increase in EGFR expression in tumor biopsies from NSCLC patients treated with RET inhibitors who experienced disease progression, further validating the clinical relevance of our findings. Conclusions This study elucidates EGFR's role in mediating resistance to RET inhibitors in NSCLC patients. These findings offer insights into therapeutic adaptation and explore personalized combinations of RET and EGFR inhibitors for improved clinical outcomes.